1990
DOI: 10.1111/j.1600-0447.1990.tb05297.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile of remoxipride ‐ a combined analysis of a comparative double‐blind multicentre trial programme

Abstract: Nine double‐blind studies comparing remoxipride to haloperidol in the treatment of acute schizophrenia formed the basis of this analysis. All studies followed a basic protocol with the main assessments performed regularly during the 4–6 week trial period according to the same methodology, thus allowing the data to be pooled. The results showed that remoxipride in a daily dose of 150–600 mg had a therapeutic effect comparable to that of haloperidol (5–45 mg/day), both on positive and negative symptoms. There wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
1

Year Published

1992
1992
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(50 citation statements)
references
References 16 publications
1
48
0
1
Order By: Relevance
“…It is a selective D2-dopamine receptor antagonist [3]. Controlled clinical trials have shown that remoxipride has a good antipsychotic effect, with a significantly lower frequency of extrapyramidal symptoms compared with haloperidol [4,5]. The effect of remoxipride on plasma prolactin elevation is short-lasting [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…It is a selective D2-dopamine receptor antagonist [3]. Controlled clinical trials have shown that remoxipride has a good antipsychotic effect, with a significantly lower frequency of extrapyramidal symptoms compared with haloperidol [4,5]. The effect of remoxipride on plasma prolactin elevation is short-lasting [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…110 However, a lower risk of acute EPS compared with conventional antipsychotics (principally haloperidol) has been consistently demonstrated in comparative clinical trials for drugs such as clozapine, 111,112 remoxipride, 113,114 risperidone, 115,119 sertindole, 120 olanzapine 121 and amisulpride. 122 The safety profiles of the atypical drugs differ in respect of non-neurological side-effects.…”
Section: Adverse Effectsmentioning
confidence: 99%
“…Although remoxipride is no longer on the market it should be mentioned that it-as predicted from preclinical studies-induced less EPS than classical APDs in equieffective doses in controlled clinical trials (review by Lewander et al 1990;Owens 1996). Whether remoxipride is comparable to some of the other novel APDs in showing EPS at placebo level is likely, but cannot be answered due to lack of appropriate placebo-controlled clinical trials.…”
Section: Eps Potential Versus Clinical Efficacy On Positive Psychoticmentioning
confidence: 99%